Hidup Hijau di Tepi Air: Menguji Punggol Waterway Terraces sebagai Model Desain Apartemen Ramah Lingkungan di Singapura - Gunawan Tanuwidjaja; Audrey Ryuka Puspita Darmosugondo; Priscilla Allodya Mintalangi (ATRIUM: Jurnal Arsitektur, 2024)
Title: Green Living by the Water; Testing Punggol Waterway Terraces as a Model for Eco-Friendly Apartment Design in Singapore This research discusses the importance of green architecture and green low-cost apartments in addressing the discord between the environment and society, particularly in developing new cities like the National Capital of Nusantara. This concept began gaining recognition in 2013 in Singapore, which has adopted the principles of Green Building. One successful example is the Punggol Waterway Terraces Apartment, which emphasizes sustainable design while considering resource efficiency and social inclusivity. Although this concept offers significant benefits, several challenges remain, including costs, accessibility, and efficiency. This study proposes research on the Green Low-Cost Apartment concept, focusing on the Punggol Waterway Terraces Apartment as a successful example. The research method used is Case Study Research, and the results highlight the design, facilities, costs, and innovations related to this concept. Punggol Waterway Terraces is part of Punggol Eco-town, a sustainable and innovative solutions laboratory. However, some weaknesses, such as lack of building maintenance and privacy, must be addressed. Nonetheless, this apartment demonstrates HDB's seriousness in realizing the concept of 'Green Living by the Waters' by implementing various green technologies and good social facilities. Thus, this apartment becomes a successful case study supporting sustainable development in Singapore.